Decree No. 96/1982 Promulgating The executive regulations of the Companies Law No. 159/1981. (2025)
Decree No. 96 of the year 1982 promulgating the Executive Regulations of Law No. 159 of the year 1981 on Joint Stock Companies, Partnerships Limited by Shares and Limited Liability Companies. Part One: On foundation of companies. - Chapter - 1: Foundation of joint stock companies and partnerships limited by shares. - Section : 1 General provisions. - Section : 2 Establishment through public subscription. - Section : 3 On the quotas in kind and the constituent assembly. - Section : 4 On foundation of companies through procedure other than public subscription. - Section : 5 On the procedures of submitting the applications for establishing joint stock companies and partnerships limited by shares and the committee concerned with reviewing the applications. - Chapter 2: On establishing limited liability companies. - Section : 1 General provisions. - Section : 2 On the heads of agreement and deed of association. - Section : 3 On capital and quotas. - Chapter – 3: Registration and publication procedures and services charge. -- Part Two :On the provisions connected with forms of companies. - Chapter 1: The joint stock companies and partnerships limited by shares. - Section : 1 Financial structure. - First : Formation, increase, reduction and depreciation of the capital. - Second : Securities issued by the company. - Third : The company's financial year distribution of profits and reserves. Section : 2 The company's management. - First: The general assembly. - Second: The board of directors of the joint stock companies. - Third : The managing partner(s) and the control council in the partnerships limited by shares. - Section : 3 The auditors. - Chapter - 2: The limited liability company - Section : 1 The financial structure. - Section : 2 The company's management -- Part Three: Merger and changing the company's form. - Chapter 1: The merger - Chapter 2: Changing the company's form. -- Part Four: Control and inspection. - Chapter - 1: Control - rights of review. - Chapter - 2: Some of the inspection procedures. - Part Five : Foreign companies' branches and representative offices - Chapter - 1: Foreign companies' branches. - Chapter - 2: The representative offices and the like. -- Part Six : Concluding and transitional provisions. Decree No. 25 Of The Year 1998 : Implementing certain provisions of law No. 3 of the year 1998 concerning the amendment of certain provisions of the law on joint stock companies, partnerships limited by shares, and limited liability companies. – Decree No. 75 Of The Year 1998 : Implementing certain provisions of law No. 3 of the year 1998 concerning the amendment of certain provisions of the law on joint stock companies, partnerships limited by shares, and limited liability companies